2011
DOI: 10.1002/mnfr.201100279
|View full text |Cite
|
Sign up to set email alerts
|

Acrolein – a pulmonary hazard

Abstract: Acrolein is a respiratory irritant that can be generated during cooking and is in environmental tobacco smoke. More plentiful in cigarette smoke than polycyclic aromatic hydrocarbons (PAH), acrolein can adduct tumor suppressor p53 (TP53) DNA and may contribute to TP53-mutations in lung cancer. Acrolein is also generated endogenously at sites of injury, and excessive breath levels (sufficient to activate metalloproteinases and increase mucin transcripts) have been detected in asthma and chronic obstructive pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
128
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(131 citation statements)
references
References 218 publications
2
128
0
Order By: Relevance
“…It alters gene regulation, mucociliary transport, and alveolar barrier integrity, which ultimately causes acute lung injury, chronic obstructive pulmonary disease (COPD), and possibly asthma and lung cancer. 11,12 Acrolein is reported to induce oxidative stress thereby causing mitochondrial dysfunction in brain cells. 13 Previous studies showed that acrolein can form acrolein adducts with cellular components, particularly proteins and DNA, which have been detected in plasma of patients with renal failure, [14][15][16][17] Alzheimer's disease, 18,19 diabetes, 14,20 and atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…It alters gene regulation, mucociliary transport, and alveolar barrier integrity, which ultimately causes acute lung injury, chronic obstructive pulmonary disease (COPD), and possibly asthma and lung cancer. 11,12 Acrolein is reported to induce oxidative stress thereby causing mitochondrial dysfunction in brain cells. 13 Previous studies showed that acrolein can form acrolein adducts with cellular components, particularly proteins and DNA, which have been detected in plasma of patients with renal failure, [14][15][16][17] Alzheimer's disease, 18,19 diabetes, 14,20 and atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Acr 2 is also a by-product of lipid peroxidation generated endogenously in cells under oxidative stress (2). Inhaled Acr is extremely toxic in mouse models (3). In fact, the effects of Acr on lung carcinogenicity in mouse models have not been assessed due to excessive death of Acr-exposed mice (3).…”
mentioning
confidence: 99%
“…Inhaled Acr is extremely toxic in mouse models (3). In fact, the effects of Acr on lung carcinogenicity in mouse models have not been assessed due to excessive death of Acr-exposed mice (3). Nonetheless, it has been shown that intraperitoneal injection of Acr causes bladder tumors in rat models (4 -7).…”
mentioning
confidence: 99%
“…Acrolein (2-propenal) is a highly reactive α, β-unsaturated aldehyde and a respiratory irritant that is ubiquitously present in the environment but that can also be generated endogenously at sites of inflammation [1,2] . Acrolein is abundant in tobacco smoke, which is the major environmental risk factor for asthma and chronic obstructive pulmonary disease (COPD), and elevated levels of acrolein are found in the lung fluids of asthma and COPD patients [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Acrolein is abundant in tobacco smoke, which is the major environmental risk factor for asthma and chronic obstructive pulmonary disease (COPD), and elevated levels of acrolein are found in the lung fluids of asthma and COPD patients [1][2][3]. Because of its reactivity with respiratory-lining fluid or cellular macromolecules, acrolein alters gene regulation, inflammation, mucociliary transport, and alveolar-capillary barrier integrity [1].…”
Section: Introductionmentioning
confidence: 99%